Developers Shift to Dynamic Programming Languages. - Paulson, Linda Dailey (Computer (00189162), 2007)
The article discusses the increased use of dynamic computer languages rather than static computer languages. Typing is the main factor in determining whether a language is static or dynamic. With statically typed languages, programs explicitly declare, but not define, variables before they are used. With dynamically typed languages, programs must define variables, but not explicitly declare them, before they are used. Static languages are usually strongly typed, while dynamic languages use usually weakly typed. According to the author, the weakly typed static languages give programmers more flexibility and quicker results. A chart on the top ranking computer languages in terms of usage is included.